The Impact of Competition on Information Technology Usage: A Cross-Industry Study of Australian Listed Companies and Industries - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2001)
This study examines the relationship between the degree of competition and IT usage in 19 selected Australian industries. An Industry Competition Measurement (ICM) Framework is used to measure the degree of competition and Information Technology (IT) usage is gauged from three indicators: critical dimensions of IT, drivers of IT investments, and the distribution of IT portfolios in these industries. Linear regression tests show a strong and significant association between the level of industry competition and the critical dimensions of IT such as impact and importance of IT. Industry competition, however, is not significantly associated with the level of motivation in investing in IT and the distribution of IT portfolio. The implication of this finding is that with increasing levels of competition, there is a need to better understand the position and role of IT. Firms in competitive industries may be at a competitive disadvantage if the position and role of IT in the firm is minimal. In addition, the cross-sectional nature of this study provided a unique view of the various inter-relationships between the degree of competition and indicators of IT usage.